Disparities in rural-vs-urban achievement of millennium development goals in Cambodia: implications for current and future child health. (2nd October 2018) - McClure, Karen; Jun, Jeany K.; Johnson, Casey R.; Fischer, Philip R.; Lu, Lydia; Vy, Sophakna; Knutson, Dale
ABSTRACT: Background : Cambodia has made significant economic, political, and health advancements with the implementation of the millennium development goals (MDG). Important gaps in child health still exist, however, and accurate assessments of lingering disparities within the country will be essential for meeting the Sustainable Development Goals by 2030. Aim: This investigation hypothesised that child-health improvements in rural areas of Cambodia continue to lag behind urban areas. The study objective was to identify specific disparities in rural achievement of MDG within Cambodia to direct future work in child health. Methods: Surveys were conducted in 230 rural households in four villages in Kampot and Kampong Speu provinces to assess risk factors contributing to lack of village-level achievement of MDG. National urban and rural data were used for comparison. Results: An under-5 death in the preceding year was reported by 11.5% ( n  = 26) of the households surveyed. Under-use of common public health interventions (vaccinations, clean drinking water, oral rehydration therapy, iodised salt, bed nets, antenatal care, and improved sanitation facilities) was observed in all villages. Under-use of the interventions was more common in rural than urban areas. Conclusion: Achievement of child-health-related MDG lags in rural areas of Cambodia. Child health risk factors varied widely among villages. Village-specific risk factors for which immediate action can be taken are a priority, particularly vaccination in Angkcheay and Takoa and clean drinking water in Pos Pong. Elimination of disparities in rural child health will ultimately require significant resource allocation in rural areas, e.g. improved sanitation facilities, piped water supply and sustained public health initiatives.